(untitled) (Circe de clásicos y modernos, 2020)
The aim of this paper is to establish the meaning of the notions of verisimilitude (τὸ εἰκός) and necessity (tò τὸ ἀναγκαῖον) in the formula “according to verisimilitude or according to necessity”, which plays an important role in the rules presented by Aristotle in his Poetics. The former notion is much less problematic than the latter, whose examination and clarification demand that attention be paid to passages in Aristotle’s work that have not been (or almost have not been) taken into account in this regard. An attempt is made to show the affinity or ultimate identity in the Aristotelian vi-sion of action in the domains of poetics and ethics, and to establish the conceptual relationship that is sugges-ted to exist between both notions in the Poetics.